Greenhouse gas accounting for landfill diversion of food scraps and yard waste. Issue 1 (2nd January 2016) - Brown, Sally
ABSTRACT: Diverting organics from landfills to compost piles is generally recognized as a means to reduce greenhouse gas emissions. This article provides a detailed review of the Climate Action Reserve (CAR) and the U.S. EPA Waste Reduction Model (WARM) protocols on landfill diversion and composting for food scraps and yard waste. The primary benefits associated with diversion are methane avoidance. The equations used to quantify methane avoidance include first-order decay rate constants for different feedstocks to predict how quickly organics will decay. The total methane generation potential of the different feedstocks is also included. The equations include estimates of gas collection efficiencies in landfills. The decay rate constants have been determined from laboratory incubations and may not be representative of decomposition within a landfill. Estimates of gas capture efficiency have been improved and more closely reflect actual landfill conditions. Gas capture efficiency will vary based on landfill cover material, portion of the landfill where measurements take place, and whether the gas collection system is operational. Emissions during composting are included in these calculations. Only the WARM model includes a consideration of benefits for compost use. Nevertheless, significant benefits are recognized for landfill diversion of food scraps. The WARM model suggests that landfilling yard waste is superior to composting.